Strategi Dalam Peningkatan Olahan Pastry Dan Bakery Di Hotel Best Western Premier The Hive Cawang Jakarta Timur - Purwanto, Eko Obi; Anggraeni, Jesica Yopi; Candrasari, Ati; Puspita, Ratna; Putra, Nova Yudha Andriansyah (LPPM Universitas Nusa Mandiri, 2022)
Food and Bakery is one of the departments in the F&B product in a hotel which is a place where various processed cakes and breads are processed which guests will enjoy. A baker must have a disciplined, agile, creative attitude and must always innovate. to always develop existing preparations into new products so that customers or connoisseurs of pastry and bakery preparations are increasingly interested and want to try these processed products, especially since processed pastry and bakery products are always a dessert. To find out the efforts to improve pastry and bakery products at the Bast Western Premier Hotel The Hive Cawang, East Jakarta, the researchers conducted research directly to the hotel. The research method used to conduct this research was descriptive qualitative analysis. The results of this study, the researchers concluded that in the processing of pastry and bakery every employee, both staff and deily workers, must follow existing management standards and recipes, both good quality raw materials, dosage, and processing techniques that aim to produce processed pastry and bakery products that are of good quality and in accordance with the standards that have been set so that there are more efforts to improve processing related to F&B at the hotel